2015
DOI: 10.3390/rs70708655
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bi-National Great Lakes Coastal Wetland and Land Use Map Using Three-Season PALSAR and Landsat Imagery

Abstract: Methods using extensive field data and three-season Landsat TM and PALSAR imagery were developed to map wetland type and identify potential wetland stressors (i.e., adjacent land use) for the United States and Canadian Laurentian coastal Great Lakes. The mapped area included the coastline to 10 km inland to capture the region hydrologically connected to the Great Lakes. Maps were developed in cooperation with the overarching Great Lakes Consortium plan to provide a comprehensive regional baseline map suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 35 publications
2
82
2
Order By: Relevance
“…Advanced techniques such as SAR-Optical fusion (Bourgeau-Chavez et al, 2015), Classification Tree Analysis (CTA), and Stochastic Gradient Boosting (SGB) (Baker et al, 2006) have shown success in mapping wetlands. However, mainly due to their seasonal variability, manual interpretation may be favoured for small areas using TC transformations (Fickas et al, 2016).…”
Section: Wetlandsmentioning
confidence: 99%
“…Advanced techniques such as SAR-Optical fusion (Bourgeau-Chavez et al, 2015), Classification Tree Analysis (CTA), and Stochastic Gradient Boosting (SGB) (Baker et al, 2006) have shown success in mapping wetlands. However, mainly due to their seasonal variability, manual interpretation may be favoured for small areas using TC transformations (Fickas et al, 2016).…”
Section: Wetlandsmentioning
confidence: 99%
“…The U.S. Environmental Protection Agency (EPA) has a regulatory mission related to air and water quality and a long history of supporting large-area assessments of resource status, which includes the work described by Bourgeau-Chavez and colleagues [73]. Their efforts support a binational (U.S. and Canada) assessment of coastal wetlands within the basin surrounding the North American Great Lakes.…”
Section: Purpose Of This Special Issuementioning
confidence: 99%
“…Alternatively, many studies have relied on microwave imagery to map flood levels [24][25][26][27]. Radar sensors have several advantages over optical and thermal ones that make them particularly applicable to monitoring hydrologic conditions of wetlands.…”
Section: Introductionmentioning
confidence: 99%